The transformation of the nuclear nanoarchitecture in human field carcinogenesis. (5th May 2017) - Bauer, Greta M; Stypula-Cyrus, Yolanda; Subramanian, Hariharan; Cherkezyan, Lusik; Viswanathan, Parvathi; Zhang, Di; Iyengar, Radha; Bagalkar, Saurabh; Derbas, Justin; Graff, Taylor; Gladstein, Scott; Almassalha, Luay M; et al.
Morphological alterations of the nuclear texture are a hallmark of carcinogenesis. At later stages of disease, these changes are well characterized and detectable by light microscopy. Evidence suggests that similar albeit nanoscopic alterations develop at the predysplastic stages of carcinogenesis. Using the novel optical technique partial wave spectroscopic microscopy, we identified profound changes in the nanoscale chromatin topology in microscopically normal tissue as a common event in the field carcinogenesis of many cancers. In particular, higher-order chromatin structure at supranucleosomal length scales (20–200 nm) becomes exceedingly heterogeneous, a measure we quantify using the disorder strength ( Ld ) of the spatial arrangement of chromatin density. Here, we review partial wave spectroscopic nanocytology clinical studies and the technology's promise as an early cancer screening technology. Lay abstract: At later stages of cancer development, abnormalities in the nucleus of cancer cells are easily detectable with conventional microscopy techniques. However, there is evidence that nuclear changes are present at a much earlier stage of cancer development. Our lab developed a novel technique, partial wave spectroscopic microscopy, which can identify changes in the nanoscale chromatin topology of otherwise normal looking cells as a common event in the progression to cancer. Here, we provide a review of our technology and its promise as an early cancer screening technology for numerous types of cancer.